AN ANALYSIS OF FIGURATIVE LANGUAGE IN DEMI LOVATO’S SONG LYRICS - Sondakh, Rati; Samola, Nurmin; Damopolii, Veronika L. F. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this study is to identify the types and meaning of figurative language used in selected song lyrics by Demi Lovato in album “Dancing with the Devil, The Art of Starting Over”. This research applied descriptive qualitative approach. The data were collected by primary sources that is listen to the song and take note the lyrics that contains of figurative language. In analyzing data, the writer used steps by Miles and reduction, data display and conclusion. The result of data analysis, there are 19 expressions of hyperbole, 27 expressions of metaphor, 5 expressions of personification, and 5 expressions of simile. The figurative language used in Demi Lovato’s song lyrics represented a various meaning they are about: loneliness, sadness, anxiety, regretful, love, life, and friendship. The writer suggests for future researcher to analyze and discuss about other types of figurative language which are not found in this study or using other theories to conduct their next study.